2015
DOI: 10.1007/s00264-015-2927-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for young adult hip dysplasia: joint-preserving options

Abstract: Developmental dysplasia of the hip (DDH) is a spectrum of disorders that results in anatomic abnormalities leading to increased contact stress in the joint and, eventually, secondary osteoarthritis. However, many patients with DDH become symptomatic before the severe degenerative changes of the hip because of abnormal hip biomechanics, mild hip instability, impingement, or associated intra-articular pathology. Early diagnosis and appropriate treatment for DDH are of the utmost importance. With the modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 79 publications
0
13
0
6
Order By: Relevance
“…With increasing age, the associated deformities can become more complex, necessitating increasingly aggressive treatments including open reduction and femoral or pelvic osteotomy [3]. For symptomatic DDH in young adults, joint-preserving surgeries such as hip arthroscopy, periacetabular osteotomy (PAO), femoral head-neck junction osteochondroplasty combined with PAO, intertrochanteric osteotomy, or capsular arthroplasty are recommended to patients with minimal articular cartilage degeneration, as they could reduce or delay the degeneration of the hip joint [4]. A recent systematic review revealed that hip arthroscopy for borderline DDH with capsular plication improved short-term patient-reported outcome measures [5].…”
Section: Discussionmentioning
confidence: 99%
“…With increasing age, the associated deformities can become more complex, necessitating increasingly aggressive treatments including open reduction and femoral or pelvic osteotomy [3]. For symptomatic DDH in young adults, joint-preserving surgeries such as hip arthroscopy, periacetabular osteotomy (PAO), femoral head-neck junction osteochondroplasty combined with PAO, intertrochanteric osteotomy, or capsular arthroplasty are recommended to patients with minimal articular cartilage degeneration, as they could reduce or delay the degeneration of the hip joint [4]. A recent systematic review revealed that hip arthroscopy for borderline DDH with capsular plication improved short-term patient-reported outcome measures [5].…”
Section: Discussionmentioning
confidence: 99%
“…These bony anomalies are accompanied with soft tissue changes such as transverse orientation of the abductor muscles, shortening of the hamstring and sciatic nerve. 2 Review of literature shows results varying from well-functioning hips for decades 12,13 to reports of frequent failures, [14][15][16] mainly due to femoral head necrosis (up to 50%), 12,16 joint stiffness (up to 30%) 13,17 and deficient coverage and redislocation (up to 15%). 12,17 Ganz et al's 5 modification involves surgical hip dislocation followed by acetabular reaming and capsulotomy via a T-shaped incision as close to the acetabular rim as possible.…”
Section: Discussionmentioning
confidence: 99%
“…3 Treatment of DDH diagnosed after 10 years of age is extremely difficult because of the soft tissue and bone deformities. 2,4 In the 20th century, joint preservation was the mainstay of surgical treatment. Options for joint preservation include techniques like pelvic osteotomy and capsular arthroplasty, femoral head-neck junction, osteochondroplasty and femoral head reduction osteotomy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations